Interspecific association patterns of woody species in an evergreen broadleaved forest of Con Dao National Park, Vietnam - Hong Hai, Nguyen; Manh, Vu; Thanh Trang, Pham; Van Quy, Nguyen (Journal of Forestry Science and Technology, 2024)
The interspecific associations among tree species in natural forest stands help to reveal mechanisms for maintaining species diversity and provide theoretical foundations for vegetation restoration and regeneration. This study focused on woody species within a 4-ha study plot established in an evergreen broadleaved forest in Con Dao National Park, Vietnam. We analyzed the interspecific associations among sixty-four recorded woody species in the study plot based on their presence and absence in subplots at two sampling scales: 10 m × 10 m and 20 m × 20 m. The results indicated that most of the 3,969 pairs of the sixty-four species exhibited independent associations, confirming an individualistic hypothesis proposed by Gleason. Furthermore, species interactions of common species were stronger than those of rare ones, indicating that species abundance influenced interspecific associations, and this result acknowledges the presence of random processes in driving species coexistence. A comparison of observed communities and random communities based on null models revealed that deterministic processes play a dominant role in governing species co-occurrence within the tree communities in the study area. Our study provides insights into the complex dynamics of species interactions within forest ecosystems, contributing to our understanding of biodiversity maintenance and offering valuable guidance for conservation and restoration efforts.